Competitiveness Assessment of Tourism in Sierra Leone : A Cluster-Based Approach - Shakya, Mallika (2012)
Seven years out of brutal conflict, Sierra Leone is now a peaceful and stable country. Yet, its strides toward economic recovery and competitiveness have been modest even in sectors such as tourism, which used to be a major generator of foreign exchange revenues prior to the conflict. This paper presents a cluster-based analysis of the tourism sector in Sierra Leone. The analysis shows that tourism in Sierra Leone draws entirely on basic factor conditions such as natural endowments; high-end lodging, catering, and entertainment services are virtually nonexistent. The cluster mapping exercise reveals that several non-profit organizations are present and active within the Sierra Leone tourism cluster but that the role of commercial enterprises has been somewhat limited. A critical mass of basic service providers has emerged over time, but their functions are often hindered by the absence of a market-based incentive regime and weaknesses in backbone infrastructure services. There is a mismatch of effort by the public and private sectors. An important policy implication arising from the analysis is for Sierra Leone to initiate a joint action among tourism entrepreneurs and policymakers to develop a coherent business strategy toward overcoming the bottlenecks of skill deficiency, policy ineffectiveness, and lack of infrastructure and market access.